2004
DOI: 10.2320/matertrans.45.2042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dislocations on the Oxygen Ionic Conduction in Yttria Stabilized Zirconia

Abstract: Ionic conductivities of yttria-stabilized zirconia (YSZ) single crystals deformed at high-temperature were measured by the AC impedance method. A correlation between ionic conductivity and dislocation structures of deformed YSZ single crystals were investigated. Electrical conductivity measurements of the deformed YSZ crystals were performed for two different current directions of [1 1 10] and [ 1 1 1 11]. The [1 1 10] direction is parallel to edge dislocations introduced by the primary slip system, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
(30 reference statements)
5
37
0
Order By: Relevance
“…48). In addition, as oxide nanocomposites are increasingly used in solid oxide fuel cells and oxygen separation membranes 7 , the TiO 2 -terminated interface can serve as a model system for assessing the role of pipe diffusion for conductivity, as observed in yttria-stabilized zirconia 49 . In contrast, the SrOterminated interface does not exhibit such behaviour, with vacancies concentrated in terraces separated by dislocations that act as barriers for migration.…”
Section: Discussionmentioning
confidence: 99%
“…48). In addition, as oxide nanocomposites are increasingly used in solid oxide fuel cells and oxygen separation membranes 7 , the TiO 2 -terminated interface can serve as a model system for assessing the role of pipe diffusion for conductivity, as observed in yttria-stabilized zirconia 49 . In contrast, the SrOterminated interface does not exhibit such behaviour, with vacancies concentrated in terraces separated by dislocations that act as barriers for migration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the compression axis was slightly tilted to be the h112i direction, and it was selected as a compression axis. 14,15) In this case, although the compression axis is tilted by 55 against the {001} plane and its Schmidt factor is 0.47, the single slip is expected in the beginnings of deformation. In this study, the dislocation density and its arrangement were controlled by compression deformation tests systematically at various temperatures and at different strain rates.…”
Section: Dislocation Control In Ysz and Ionic Conductivitymentioning
confidence: 99%
“…Figure 7 shows the microstructure with strain amount of (a) 1% and (b) 10% in the case where deformation was made at the temperature of 1300 C at the strain rate of 8 Â 10 À6 s À1 , respectively. 14,15) The observations were made along the ½1 1 10 direction, in which the Fig. 7 Bright field images of the dislocation structures for the specimens deformed up to (a) 1% and (b) 10% strain with the incident beam parallel to the ½1 1 10 direction, which is parallel to the dislocation lines introduced by primary slip.…”
Section: Dislocation Control In Ysz and Ionic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…22),23) Otsuka et al reported that the dislocation line also acts as a rapid diffusion path. 24), 25) The impurity segregation along grain boundaries also affects the YSZ properties.…”
Section: Introductionmentioning
confidence: 99%